Enter a problem...
Algebra Examples
2x-3y=62x−3y=6
Step 1
Subtract 2x2x from both sides of the equation.
-3y=6-2x−3y=6−2x
Step 2
Step 2.1
Divide each term in -3y=6-2x−3y=6−2x by -3−3.
-3y-3=6-3+-2x-3−3y−3=6−3+−2x−3
Step 2.2
Simplify the left side.
Step 2.2.1
Cancel the common factor of -3−3.
Step 2.2.1.1
Cancel the common factor.
-3y-3=6-3+-2x-3
Step 2.2.1.2
Divide y by 1.
y=6-3+-2x-3
y=6-3+-2x-3
y=6-3+-2x-3
Step 2.3
Simplify the right side.
Step 2.3.1
Simplify each term.
Step 2.3.1.1
Divide 6 by -3.
y=-2+-2x-3
Step 2.3.1.2
Dividing two negative values results in a positive value.
y=-2+2x3
y=-2+2x3
y=-2+2x3
y=-2+2x3